2012
DOI: 10.1111/j.1529-8019.2012.01478.x
|View full text |Cite
|
Sign up to set email alerts
|

Nonablative fractional photothermolysis for acne scars: clinical and in vivo microscopic documentation of treatment efficacy

Abstract: Fractional photothermolysis has been shown to improve various types of scarring, including atrophic acne scars. The aim of the present authors was to assess the efficacy and safety of the nonablative fractional photothermolysis in the treatment of moderate and severe acne scars. Eighty-seven patients with moderate or severe acne scarring were treated with six sessions with a 1540-nm Erbium glass fiber laser at 3-week intervals. Six months after the final session, 7/87 (8%) patients showed a moderate improvemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 15 publications
3
35
0
1
Order By: Relevance
“…A large study of 87 Italian patients (skin types I-V) revealed a greater than 50% improvement in atrophic scars in 89% of patients after 3 months and in 92% of patients after 6 months. 52 Similar studies in Asian patients corroborate these results. 53 The Er:glass has been shown to perform best on boxcar scars (52.9% improvement), followed by rolling (43.1% improvement) and ice-pick scars (25.9% improvement).…”
Section: Acne Scarringsupporting
confidence: 61%
“…A large study of 87 Italian patients (skin types I-V) revealed a greater than 50% improvement in atrophic scars in 89% of patients after 3 months and in 92% of patients after 6 months. 52 Similar studies in Asian patients corroborate these results. 53 The Er:glass has been shown to perform best on boxcar scars (52.9% improvement), followed by rolling (43.1% improvement) and ice-pick scars (25.9% improvement).…”
Section: Acne Scarringsupporting
confidence: 61%
“…Epidermal changes and collagen remodeling were evaluated by in vivo confocal microscopy [22]. Recently, Sattler et al treated healthy probands with fractional carbon dioxide laser; then the optical follow-ups were performed using confocal laser scanning microscopy and optical coherence tomography right after laser application and during the following 3 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Several retrospective and randomized controlled trials of acne scar treatment 14,15 have shown long-term improvement in skin texture after nonablative fractional photothermolysis. Nonablative fractional lasers produce long-term collagen remodeling in burn scars and surgical scars.…”
Section: Evidence For Skin Tightening With Nonablative Fractional Phomentioning
confidence: 99%